2016
DOI: 10.4103/1658-354x.168807
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of caudal tramadol versus caudal fentanyl with bupivacaine for prolongation of postoperative analgesia in pediatric patients

Abstract: Background and Aims:Caudal block is a common technique for pediatric analgesia for infraumblical surgeries. Because of the short duration of analgesia with bupivacaine alone various additive have been used to prolong the action of bupivacaine. The present study was aimed to evaluate the analgesic effect of tramadol or fentanyl added to bupivacaine for infraumblical surgeries in pediatric patients.Materials and Methods:We conducted a prospective, randomized, single-blind controlled trial. After written informed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 16 publications
2
13
0
Order By: Relevance
“…We did not observe any serious adverse effects, and our minor complication rates were very low, and comparable in the two studied groups. These results are in agreement with studies which reported the safety of caudal tramadol [ 28 31 ].…”
Section: Discussionsupporting
confidence: 93%
“…We did not observe any serious adverse effects, and our minor complication rates were very low, and comparable in the two studied groups. These results are in agreement with studies which reported the safety of caudal tramadol [ 28 31 ].…”
Section: Discussionsupporting
confidence: 93%
“…This is desirable as the child is more calm and comfortable in the immediate postoperative period. 21 The duration of urinary retention in case of group-T was found to be 8.25±1.41 hours and in group-F was found to be 6.41±1.48 hours which was significantly longer in group T. In present study two identical twins who underwent urethroplasty for hypospadiasis both had a slightly longer sacral hiatus as compared to other children. Similar duration of analgesia in both the children (12 and 12.2 hours) was observed.…”
Section: Discussionsupporting
confidence: 40%
“…Post-operatively pain scale was monitored at 2,4, 6,12 [2] and 24 hours by using CHIPPS scale. Postoperatively monitored for blood pressure, heart [3] rate at 2, 4,6,12 and 24 hours. Side effects.…”
Section: Methodsmentioning
confidence: 99%
“…Caudal block is one of the main modes of posto-perative analgesia in children for infra umbilical surgeries [1]. Local anaesthetics which are commonly used in the caudal block are bupivacaine, levobupivacaine, and ropivacaine in different concentrations with additives like fentanyl, morphine, butorphanol, tramadol, clonidine, dexmedetomidine and dexamethasone which are added to improve their efficacy [2,3]. Epinephrine 1:200000 concentrations mixed with local anaesthetics marginally prolonged the effect of hydrophilic lignocaine but failed to do so with lipophilic bupivacaine due to its fat absorption and slow release [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation